2021
DOI: 10.3390/land10040339
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathways: The Influence Mechanism of Greenspace Exposure on Mental Health—A Case Study of Hangzhou, China

Abstract: Greenspace exposure (GSE) may have a positive impact on mental health. However, existing research lacks a classification analysis of the influence pathways of different GSE on mental health. Meanwhile, the research method is limited to the measurement of the green space ratio (GSR) based on remote sensing data, which ignores people’s real perception of greenspace. This paper aims to further expand the measurement method of GSE, taking Hangzhou, China as an example, and to reveal the influence mechanism of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…As the provincial capital and central city of the Yangtze River Delta, Hangzhou has always been the center of social, economic, and cultural development in Zhejiang Province. Related research has shown that since the Reform and Opening Up, especially in the past 20 years, Hangzhou's economy has rapidly developed (Lu et al, 2021), with the urban land area increasing annually (Figure 7). This has become the main driving force for shifting the gravity center of urban land to the northwest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the provincial capital and central city of the Yangtze River Delta, Hangzhou has always been the center of social, economic, and cultural development in Zhejiang Province. Related research has shown that since the Reform and Opening Up, especially in the past 20 years, Hangzhou's economy has rapidly developed (Lu et al, 2021), with the urban land area increasing annually (Figure 7). This has become the main driving force for shifting the gravity center of urban land to the northwest.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5a This reveals that, concerning geographic location, the urban land and carbon emissions were not evenly distributed. Hangzhou's economy has rapidly developed (Lu et al, 2021), with the urban land area increasing annually (Figure 7). This has become the main driving force for shifting the gravity center of urban land to the northwest.…”
Section: Spatial Characteristicsmentioning
confidence: 99%
“…In the process of individual socialization, the harmonious development of personality constitutes the core component of the overall quality. The criteria of personality health include at least three aspects: good realistic perception, a good understanding of self, and a positive attitude towards life [ 12 ]. A person with a healthy personality can correctly understand the real environment, have appropriate behavior and emotional response, have a good interpersonal relationship, can be self-pleasing, have basic accurate self-expression cognition and no inferiority, and can adjust and control your emotions; able to face life with a positive attitude, dare to bear setbacks, dare to overcome difficulties, and have good behavior.…”
Section: Mental Health Educationmentioning
confidence: 99%
“…There is a basic contradiction between adaptation and development, and the imbalance of this contradictory relationship will inevitably lead to mental health [ 15 ]. Psychological education focuses on the development of students' potential so as to drive the overall progress of students [ 12 ].…”
Section: Mental Health Educationmentioning
confidence: 99%
“…Various researches have been conducted on the development of road greening in Karachi. These studies focused on the ecological functions of road greening plants [7][8][9], overall effects [10], planting patterns [11][12], community structure, etc., and from the outside, the road plants can fix carbon and release carbon. Oxygen, improving the environment, and forming life materials in different seasons are unique.…”
Section: Introductionmentioning
confidence: 99%